Study of Titanium, Vanadium, Chromium and Manganese doped lead free double perovskites Cs2NaGaBr6 for potential solar cell - Hussain, Ahmed Zabir (Brac University, 2024)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Science in Physics,2024.